2021
DOI: 10.1111/ele.13763
|View full text |Cite
|
Sign up to set email alerts
|

Efficient movement strategies mitigate the energetic cost of dispersal

Abstract: Dispersal is a critical, but costly, stage of life. During the active phase of dispersal—called transience—individuals face many costs, from increased mortality to reduced foraging opportunities. One cost that is often assumed, but rarely explicitly tested, is the energy expended in making large dispersal movements. However, this cost is not only determined by the distance individual’s move, but also how they move. Using high‐resolution GPS tracking of dispersing and resident vulturine guineafowl (Acryllium vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…Both lions spent considerable time outside the protected areas to the north of Hwange NP and the south of Chizarira NP, corroborating a previous analysis of human–lion conflict risk (Cushman et al, 2018). The distinct movement behaviours during transience (travelling further and straighter) may reduce the costs of large displacements and are consistent with other studies (Elliot et al, 2014; Klarevas‐Irby et al, 2021). While we have no evidence of additional lion movement between these two areas, these are potentially not unique events given the small proportion of dispersing lions collared in the two areas.…”
Section: Discussionsupporting
confidence: 90%
“…Both lions spent considerable time outside the protected areas to the north of Hwange NP and the south of Chizarira NP, corroborating a previous analysis of human–lion conflict risk (Cushman et al, 2018). The distinct movement behaviours during transience (travelling further and straighter) may reduce the costs of large displacements and are consistent with other studies (Elliot et al, 2014; Klarevas‐Irby et al, 2021). While we have no evidence of additional lion movement between these two areas, these are potentially not unique events given the small proportion of dispersing lions collared in the two areas.…”
Section: Discussionsupporting
confidence: 90%
“…obs .) due to a strong female bias in dispersal (Klarevas‐Irby et al, 2021). Relatedness also appears to play an important role in mammalian MLSs.…”
Section: Discussionmentioning
confidence: 99%
“…However, travelling itself requires energy [63] and imposes higher risk of hyperthermia and dehydration, especially during drought. Recent work on vulturine guineafowl demonstrated that dispersing subadults moved substantially more efficiently during transience, thereby achieving much larger daily displacements with little effects on their energy budget [64]. Changes in individual physiology (e.g.…”
Section: Discussionmentioning
confidence: 99%